Hyper-redundant endoscopic manipulator position compensation under external load - Giacoppo Giuliano A.; Schulze Eric; Pott Peter P. (Current Directions in Biomedical Engineering)
This paper focuses on determining the cable tension required for a cable-driven endoscopic manipulator to reach a given position under an external load at the end effector. The aim is to restore the initial position of the end effector without an external force. A simulation was performed using MATLAB, where mathematical models and algorithms were used to calculate the required tension. The mathematical model, based on Optimized Motion Estimation Analysis, considers the joint stiffness and the influence of gravity, in addition to the cable tensions and external load. The algorithm minimizes the sum of moments to achieve a stable position. An optical tracking system was used to validate the simulation results against experimental data. The manipulator successfully compensated for an external load of 1.96N and returned to its initial position with adjusted cable tensions. The results showed that the manipulator was deformed by an external load, highlighting the need to adjust the cable tension for position compensation. The discrepancies between the experimental and simulation results were due to factors such as marker size, as well as joint imperfections due to manufacturing and friction effects. Nevertheless, the proposed method proved to be effective in compensating for external loads and restoring the manipulator to the desired position.